PENGARUH STRATEGI PEMBELAJARAN TERHADAP HASIL BELAJAR PENGOLAHAN DESSERT SISWA SMK 8 MEDAN - Dinar, Frida (Universitas Negeri Medan, 2013)
ABSTRACT The Objective of this study is to find out instructional strategies used and the achievement of study by Dessert processing of student.This study was conducted at SMK Negeri 8 School Medan for even Semester of 2010/2011 academic year. The population of this research is all students of grade I group total 32 students and grade XI Boga 2 total 32 students. The instrument used for collecting the experiment Quasi method with a factorial research design of 2 x 2. the data were analized with anova on significant rate of =0.05. the result of the analysis showed that the learning outcomes Dessert Processing learning outcomes taught by learning strategies ( F = 14,438 count > F table 4.08). The result of this study concludes that the strategy of industrial traning is higher that the resulth of learning taught by the inquiry learning strategy. Kata Kunci : Strategi pembelajaran, hasil belajar.